Does the Pandemic Affect Unemployment Rate in East Java? (A Study of Pre and Post COVID-19 Pandemic in 2016 to 2021) - Mochamad Kevin Romadhona (The Journal of Indonesia Sustainable Development Planning, 2022)
This paper aimed to identify the problems caused by labor policy in the 2016 – 2020 period in the province of East Java. This study can be a response to the employment problems being experienced by the people of East Java before and after the COVID-19 pandemic in Indonesia. Thus, it is necessary to conduct further studies to provide relevant recommendations regarding appropriate labor policies. The method used in this research was the descriptive method and analytical techniques using the unemployment rate, fully employed, and underemployed formulas. The results showed that the unemployment rate in East Java in the 2019-2020 period increased significantly by 1.92%. Meanwhile, the population working full-time decreased by 3.81%, whereas the population working part-time grew by 1.9%2. This can be due to the unavailability of sufficient employment opportunities for the working-age population in East Java as well as the government policies such as large-scale social restrictions, work from home, and termination of employment relationships by many companies.